Effect of irradiated and non-irradiated waste PET based cementitious grouts on flexural strength of semi-flexible pavement - Khan, M.I. (MDPI AG, 2019)
In this study the effect of irradiated and non-irradiated waste polyethylene terephthalate (PET) as replacement of cement and fly-ash in ordinary Portland cement (OPC) and geopolymeric cement (GPC) based cementitious grouts on flexural strength of semi-flexible pavement specimens were evaluated. The porous asphalt gradation was selected based on Malaysian specifications for semi-flexible pavements with a target of 30 air voids. The cement content in the OPC grouts and the fly-ash content in the GPC based grouts were partially replaced with 1.25 PET (using both irradiated and non-irradiated PET). Beam specimens were prepared and tested for flexural strength properties using center point loading configuration. The grouts modified with recycled waste plastic (PET) showed approximately the same results as obtained from the control specimens. Although the replacement amount was low (1.25 by weight of cement), nonetheless, significant impact on reducing CO2 emissions is expected when preparing grouts for mass construction of semi-flexible pavement surfaces. Similarly, effective recycling of waste plastics in road construction and replacing OPC with plastic and geopolymers will have a positive effect on the environment and will furthermore contribute to sustainable pavement construction. Â© 2019 by the authors.